Pengembangan e-booklet “Tumbuhan Survival” sebagai sumber belajar pada materi keanekaragaman hayati - Ahnisa Nur Ridha Rahma; Muzzazinah Muzzazinah; Sri Widoretno (Universitas Sebelas Maret, 2024)
ENThe research aims to (1) Identify the results of survival plant inventory in Tlogodlingo, Tawangmangu District (2) Identify the benefits of plant inventory results in Tlogodlingo as a learning resource in the form of e-booklets (3) Identify the viability of survival plant e-booklets as a learning resource on biodiversity material. The research applied is Research and Development (R&D). Research data were collected through observation, interviews, plant descriptions, and questionnaires. Plant samples were obtained using the purposive sampling method. The data collection instrument is an expert assessment questionnaire to assess the viability of e-booklet media as a learning resource on plant classification and utilization of biodiversity. The results showed that the identification of survival plants found in Tlogodlingo, Tawangmangu District are divided into 13 plants as food and seven plants as medicine. The validation test results are valid with a percentage value of 87,5% by media expert validators, 85% by linguist validators, and 80% by material expert validators. Learning resources in e-booklets are suitable for use with significant improvements. IDPenelitian bertujuan untuk (1) Mengetahui hasil inventarisasi tumbuhan survival di Tlogodlingo, Kecamatan Tawangmangu (2) Mengetahui manfaat hasil inventarisasi tumbuhan di Tlogodlingo sebagai sumber belajar dalam bentuk e-booklet (3) Mengetahui kelayakan e-booklet tumbuhan survival sebagai sumber belajar pada materi keanekaragaman hayati. Penelitian menerapkan metode penelitian dan pengembangan atau Research and Development (R&D). Pengambilan data penelitian melalui observasi, wawancara, deskripsi tumbuhan, dan angket. Sampel tumbuhan didapatkan menggunakan metode purposive sampling. Instrumen pengumpulan data berupa angket penilaian ahli untuk menilai kelayakan media e-booklet sebagai sumber belajar pada sub-materi klasifikasi tumbuhan dan pemanfaatan keanekaragaman hayati. Hasil penelitian menunjukkan bahwa hasil identifikasi tumbuhan survival yang ditemukan di Tlogodlingo Kecamatan Tawangmangu terbagi atas 13 tumbuhan sebagai makanan dan 7 tumbuhan sebagai obat. Hasil uji validasi adalah valid dengan persentase nilai sebesar 87,5% oleh validator ahli media, 85% oleh validator ahli bahasa, 80% oleh validator ahli materi Sumber belajar berupa e-booklet layak digunakan dengan perbaikan yang berarti.